2001
DOI: 10.1023/a:1005619803917
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aim of this study was to investigate gastric accommodation to a meal in patients with reflux esophagitis using ultrasonography. Twenty consecutive patients with reflux esophagitis of grade I (14) or II (6) and 20 healthy subjects underwent ultrasonographic measurements of the stomach before and after ingestion of a 500 ml soup meal. Reflux esophagitis patients revealed a significantly larger sagittal area of the proximal stomach at 5 min (P = 0.002) and 15 min (P = 0.007) postprandially and experienced mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…13 Ultrasonography offers a safe, well-tolerated alternative to these methods. Ultrasound examination has been used to assess gastric emptying, gastric volumes, and accommodation in healthy patients, 1719 as well as in patients with functional dyspepsia, 48 diabetes, 49 gastroesophageal reflux and esophagitis, 50 recurrent abdominal pain, 51 and obesity. 52 Ultrasonography has been shown to yield comparable results to the gold standard tests, 20,21 with antral diameter providing a measure of gastric accommodation and RGV reflecting gastric emptying, and to have good reliability and reproducibility, as well as low interobserver variation and error.…”
Section: Discussionmentioning
confidence: 99%
“…13 Ultrasonography offers a safe, well-tolerated alternative to these methods. Ultrasound examination has been used to assess gastric emptying, gastric volumes, and accommodation in healthy patients, 1719 as well as in patients with functional dyspepsia, 48 diabetes, 49 gastroesophageal reflux and esophagitis, 50 recurrent abdominal pain, 51 and obesity. 52 Ultrasonography has been shown to yield comparable results to the gold standard tests, 20,21 with antral diameter providing a measure of gastric accommodation and RGV reflecting gastric emptying, and to have good reliability and reproducibility, as well as low interobserver variation and error.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that impaired GA is associated with functional dyspepsia1,8,19 whereas excessive GA is associated with gastroesophageal reflux disease 20. The impaired GA may lead to increased intragastric distribution to the antrum in functional dyspepsia 21.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from abnormalities in gastric emptying, regional disturbances in gastric motility have also been implicated in the development of GERD, although conflicting results were reported. Most studies have reported either prolonged or abnormally enhanced postprandial gastric relaxation [97,98,99]. Similar to delayed gastric emptying, an abnormal increase in proximal gastric relaxation leads to increased gastric distension and may increase the number of TLESRs.…”
Section: Gastric Dysmotilitymentioning
confidence: 99%